Phytochemicals and antioxidant activities of Sarawak Bario rice varieties - Ronie, Macdalyna Esther; Mamat, Hasmadi; Abdul Aziz, Ahmad Hazim; Zainol, Mohamad Khairi; Ridhwan, Norazlina Mohammad; Kobun, Rovina; Putra, Nicky Rahmana (Talenta Publisher, 2025)
Rice serves as a primary food source for almost half of the world’s population and is available in numerous varieties, ranging from pigmented to non-pigmented types. Compounds such as phenolic and flavonoids are well known for their antioxidant capacity and beneficial effects on health. This study investigated the TPC, TFC, and antioxidant activity, assessed through the DPPH assay, in Bario rice varieties, an indigenous crop from Sarawak, Malaysia. Results showed that pigmented varieties (BC, BT, and BMS) exhibited significantly higher TPC compared to non-pigmented varieties (TQR and BAH). At 25 mg/ml, TPC values were 8.31, 4.69, and 4.0 mg GAE/ g dry weight for BC, BT, and BMS, respectively, whereas TQR and BAH recorded 2.48 and 2.41 mg/GAE/g dry weight. A similar trend was observed in TFC, with BMS showing the highest value (3.06 mg QE/g) at 3.5 mg/ml. The DPPH assay further confirmed stronger antioxidant potential in pigmented rice, particularly BC, which achieved 59.61% inhibition at 70 mg/ml. The enhanced antioxidant capacity was attributed to the retention of rice bran, rich in phytochemicals. Overall, the findings highlight the nutritional and functional potential of Bario rice varieties, suggesting their relevance in promoting human health.